2015
DOI: 10.1017/jfm.2015.475
|View full text |Cite
|
Sign up to set email alerts
|

Regimes of tonal noise on an airfoil at moderate Reynolds number

Abstract: Tonal noise generated by airfoils at low to moderate Reynolds number is relevant for applications in, for example, small-scale wind turbines, fans and unmanned aerial vehicles. Coherent and convected vortical structures scattering at the trailing edge from the pressure or suction sides of the airfoil have been identified to be responsible for such tonal noise generation. Controversy remains on the respective significance of pressure-and suction-side events, along with their interaction for tonal noise generati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
58
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(70 citation statements)
references
References 38 publications
12
58
0
Order By: Relevance
“…The suction side dominated regime (figure 13a) is expected to occur at relatively low angles of attack, as it requires the formation of a separation bubble close to the trailing edge, which is known to move upstream with increasing angle of attack (Boutilier & Yarusevych 2012b). This is supported by recent acoustic measurements conducted in an anechoic facility by Pröbsting et al (2015). Finally, the development of a separation bubble on the suction side, which was of particular interest in the present investigation, has been shown to be influenced significantly by tonal emissions.…”
Section: Summary Of Feedback Effectsupporting
confidence: 81%
See 2 more Smart Citations
“…The suction side dominated regime (figure 13a) is expected to occur at relatively low angles of attack, as it requires the formation of a separation bubble close to the trailing edge, which is known to move upstream with increasing angle of attack (Boutilier & Yarusevych 2012b). This is supported by recent acoustic measurements conducted in an anechoic facility by Pröbsting et al (2015). Finally, the development of a separation bubble on the suction side, which was of particular interest in the present investigation, has been shown to be influenced significantly by tonal emissions.…”
Section: Summary Of Feedback Effectsupporting
confidence: 81%
“…From their onset at 10 m s −1 , shear layer vortices on the pressure side are the dominant contributors. These trends agree with those reported for acoustic measurements in an anechoic wind tunnel on a half-scale NACA 0012 model at the same angle of attack(Pröbsting, Scarano & Morris 2015).…”
supporting
confidence: 90%
See 1 more Smart Citation
“…Future developments of the present work can include new testing conditions, as per recent contributions from (Arcoundoulis et al, 2013) and (Pröbsting et al, 2015).…”
Section: Discussionmentioning
confidence: 92%
“…(1). Similarly, Pröbsting et al (2015) identified tonal noise generation on a NACA 0012 aerofoil in a range of Reynolds number from 30,000 to 230,000 and AoA from 0 to 6.3…”
Section: Introductionmentioning
confidence: 96%